HISTORICAL DEVELOPMENT OF THE TERM AND TERMINOLOGY AND SCIENTIFIC CONSIDERATIONS ABOUT THEM (Scientific journal of the Fergana State University, 2023)
This article primarily provides information about the development factors of terminology. Also, the scientific views of Uzbek and world linguists about terms and terminology are discussed in detail. In this work, attention is paid to the types of terms according to different characteristics and their examples are given. The methods of creating terms, their use in their own and figurative meanings are revealed with the help of concrete examples.